2020
DOI: 10.1007/s10488-020-01072-9
|View full text |Cite
|
Sign up to set email alerts
|

Economic Evaluations of Public Health Interventions to Improve Mental Health and Prevent Suicidal Thoughts and Behaviours: A Systematic Literature Review

Abstract: To review the literature on economic evaluations of public health interventions targeting prevention of mental health problems and suicide, to support evidence based societal resource allocation. A systematic review of economic evaluations within mental health and suicide prevention was conducted including studies published between January 2000 and November 2018. The studies were identified through Medline, PsychINFO, Web of Science,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…However, the number of patients in psychiatric special health care among children has increased by almost 80% during the last 10 years (32), despite the limitation that specialised health care is only available for severe or prolonged symptoms (33). Public health interventions aiming to improve the mental health of children and adolescent are cost‐effective (34). Without these interventions, children and adolescents may be directed to the incorrect place to obtain help.…”
Section: Introductionmentioning
confidence: 99%
“…However, the number of patients in psychiatric special health care among children has increased by almost 80% during the last 10 years (32), despite the limitation that specialised health care is only available for severe or prolonged symptoms (33). Public health interventions aiming to improve the mental health of children and adolescent are cost‐effective (34). Without these interventions, children and adolescents may be directed to the incorrect place to obtain help.…”
Section: Introductionmentioning
confidence: 99%
“…The WHO urges media professionals to be cautious when it comes to the method of suicide because it may trigger copycat behavior, especially some stories can spread like a wild fire on social media. In our study, the guideline was violated when details of Hannah's suicide plans played out on the screen, including picking up razor blades from her parents' drugstore in Episode 13.…”
Section: Plos Onementioning
confidence: 81%
“…Based on a 6:1 benefit-cost ratio, they recommended increasing investment in prevention efforts such as medical and counseling services [ 20 ]. Similarly, Feldman and colleagues suggested that public health initiatives need to be cost-effective yet uncompromising of high quality to improve mental health and prevent suicides [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review is the first to focus on model-based economic evaluations of mental health prevention. Previous systematic reviews [ 9 , 77 , 78 ] commonly addressed trial-based economic evaluation studies, examined short-term costs and consequences and did not reflect real-life practice. Thus, our search strategy was more sensitive in detecting model-based economic evaluations.…”
Section: Discussionmentioning
confidence: 99%